PENINGKATAN KOMPETENSI GURU DALAM MENULIS LAPORAN PENELITIAN TINDAKAN KELAS (PTK) BERBENTUK ARTIKEL JURNAL MELALUI PENDAMPINGAN DI MTsN 6 TULUNGAGUNG - Maryono, Maryono (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2020)
Conducting research activities is one of the competencies that should be owned by a professional teacher, this is because one of the characteristics of an effective teacher is a teacher who has a reflective nature. Classroom action research (CAR) is now one of the efforts to solve problems and improve the quality of learning that can be done by teachers in their classrooms. In the implementation of the service, the service division divides the activity method into three stages which include the planning stage, the organizing stage, the workshop implementation stage, and the evaluation phase. The training participants consisted of 14 teachers from various subject areas at MTs Negeri 6 Tulungagung. Implementation of assistance to better understand the concepts and applications of classroom action research (CAR) is carried out by lecturing, discussion and question and answer methods. The enthusiasm of the participants in asking questions was very good, it was proven that there were more than half of the participants asking questions related to CAR. While the implementation of mentoring to write a class action research report (CAR) in the form of scientific journal articles begins with a workshop on writing narrative learning in class as a form of CAR analysis, online search tracing and reference downloads, and concludes with a workshop on journal article writing based on CAR activities participants have ever carried out.